Assessing Environmental Protection In Indonesian Mining Laws - Kartikasari, Feby Ivalerina (Arena Hukum, 2025)
This research investigates the quality of Indonesian mining laws in regulating environmental protection, prompted by the ongoing environmental degradation as a consequence of mining activities. Although various laws have been introduced since the Dutch colonial era, environmental issues remain largely unresolved. This raises the key question: has the quality of current mining laws improved in ensuring environmental protection? Some studies have addressed environmental and natural resource governance in Indonesia, analysing several legal provisions that reveal weaknesses in environmental protection. However, they have not explicitly focused on evaluating the quality of the relevant laws and regulations. Unlike previous research, this study examines legal quality in depth by establishing measurable criteria for analysis. It employs a normative legal method, drawing on legis prudence literature toapply both formal and substantive quality criteria. It also incorporates internationally accepted principles for mining and environmental management. The findings reveal that Indonesia’s mining laws do not meet the legal quality criteria for environmental protection. However, Law No. 4 of 2009 has a higher level of legal quality compared to Law No. 3 of 2020. These results indicate a regression in the legal quality of environmental protection within Indonesia’s mining regulatory framework. This study contributes to legal scholarship by presenting a structured method for analysing the quality of laws and offers valuable insights into the quality of mining law in resource-rich countries, especially Indonesia.